PEMBELAJARAN TARI BEDAYO TULANG BAWANG DENGAN MENGGUNAKAN METODE DEMONSTRASI DI SMP NEGERI 16 BANDAR LAMPUNG - era aryani sasiwi; I wayan Mustika; hasyimkan hasyimkan; agung kurniawan (Jurnal Seni dan Pembelajaran, 2013)
Issues discussed in this study is learning dance Bedayo Tulang Bawang using SMP Negeri 16 demonstration in Bandar Lampung. This study aimed to describe the dance lessons Bedayo Tulang Bawang using ekstrakurikuller dance demonstration at Junior High School 16 in Bandar Lampung.This research uses descriptive qualitative method. Sources of data in this study were students of class VII ekstrakurikuller dance at Junior High School 16, Bandar Lampung, amounting to 11 students. The technique used to collect the data were observation participate (participation), interviews, documentation, and testing practices.Method applied to the study of dance demonstrations Bedayo Tulang Bawang from the initial meeting to the final meeting. Demonstration method is an appropriate method to study dance Bedayo Tulang Bawang because this method can facilitate the teacher to explain and practice a motion that can be understood by the student and the student can directly imitate and follow that practiced by the teacher.Learning outcomes Bedayo Tulang Bawang dance using the demonstration showed that the average student is able to demonstrate Bedayo Tulang Bawang dance pretty well according to you have been taught. Assessment is given through three aspects of mobility, accuracy and expression motion with accompaniment while dancing.KEY WORD : EDUCATION, BEDAYO TULANG BAWANG DANCE, DEMONSTRATIONS